(untitled) (Western European Journal of Medicine and Medical Science, 2025)
This article covers the causes of atmospheric pollution, its impact on human health, and ways to solve this problem. The article presents examples from international and national experience, revealing the relevance of the problem based on statistical data. Detailed information is provided on the impact of atmospheric pollution on health, including respiratory diseases, cardiovascular problems, and other risks